Improving The Speaking Skill Through Watching Animation Movie to The Eight Grade Students at SMP Islam Terpadu (IT) Qurrota A’yun Palu - Yun Pratiwi; Ana Kuliahana (Datokarama English Education Journal, 2021)
The aim of this research was to improve the speaking learning process of eight grade students ofSMP Islam Terpadu (IT) QurrotaA’yunPaluin the academic year of 2019/2020 through animation movie. This study was an class action research study. It was conducted in two cycles, from the 4th of March to the 12th of March 2020. Each cycle consisted of two meetings. The steps of the research were planning, action, observation, and reflection. The subjects of this research were 30 students of VIII D class, the English teacher, and the researcher. The data were in the form of qualitative data and also supported by quantitative data. The qualitative data were obtained by observing the teaching and learning process, interviewing the students and collaborators, holding discussions with the collaborators, and taking pictures of the teaching and learning process. Meanwhile, the quantitative data were obtained through post-test, the field notes and interview transcripts were analyzed qualitatively through four steps namely data collection, data reduction, data display, and conclusions. The results of this research showed that the implementation of animation movie in the speaking learning process was effective to make the students become enthusiastic in the Englishspeaking activities. The use of animation movie that was combined with speaking performances and group works made significant progress in the speaking learning process. The students were interested towards the materials, could understand the materials easily, and spoke more confidently. In reference to the number, the students who was completely the score of speaking skill was improved from 70% to 80% and the number of the students who has a high confidence in speaking was improved from 78% to 82,66%. The students’ interest level toward speaking was improved through the use of animation movies because they could learn speaking English through fun activities with their friends. Therefore, they were not bored in the teaching-learning process.